2020
DOI: 10.3390/nu12051523
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with the Leucine Metabolite β-hydroxy-β-methylbutyrate (HMB) does not Improve Resistance Exercise-Induced Changes in Body Composition or Strength in Young Subjects: A Systematic Review and Meta-Analysis

Abstract: β-hydroxy-β-methylbutyrate (HMB) is a leucine metabolite that is purported to increase fat-free mass (FFM) gain and performance in response to resistance exercise training (RET). The aim of this systematic review and meta-analysis was to determine the efficacy of HMB supplementation in augmenting FFM and strength gains during RET in young adults. Outcomes investigated were: total body mass (TBM), FFM, fat mass (FM), total single repetition maximum (1RM), bench press (BP) 1RM, and lower body (LwB) 1RM. Database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…However, Din et al found that RT combined with HMB-FA supplements in healthy older men did not increase muscle strength more than RT alone 53 . To further determine whether HMB supplementation could improve body composition, Jakubowski et al performed a meta-analysis of 11 randomized controlled trials, which indicated that HMB supplementation did not significantly improve the body composition of healthy subjects aged 18-45 years who underwent RT 54 . Our study was the first to evaluate the effect of combined RT and HMB supplementation on changes in body composition in patients with sarcopenia following joint replacement.…”
Section: Effect Of Interventions On Body Composition and Grip Strengthmentioning
confidence: 99%
“…However, Din et al found that RT combined with HMB-FA supplements in healthy older men did not increase muscle strength more than RT alone 53 . To further determine whether HMB supplementation could improve body composition, Jakubowski et al performed a meta-analysis of 11 randomized controlled trials, which indicated that HMB supplementation did not significantly improve the body composition of healthy subjects aged 18-45 years who underwent RT 54 . Our study was the first to evaluate the effect of combined RT and HMB supplementation on changes in body composition in patients with sarcopenia following joint replacement.…”
Section: Effect Of Interventions On Body Composition and Grip Strengthmentioning
confidence: 99%
“…35 HMB had minimal effect on total body mass gain when combined with an exercise regimen in the elderly, and this effect was not reflected in greater increases in fat-free mass, strength, or decreases in fat mass. 36 Authors suggested the HMB has no beneficial effect on the improvement of body composition or strength when added to the resistance training exercise regimen. These results are consistent with our observation indicating that HMB and exercise had no interactive effect on body composition: Exercise did not have any robust effect on body composition in addition to the effect of the HMB supplementation and vice versa.…”
Section: Interactive Effects Of Hmb and Exercise On Body Weight And B...mentioning
confidence: 99%
“…Leucine and its metabolite HMB have been shown to stimulate muscle anabolism in several animal models, but also in specific situations in humans [8]. However studies that show no effect on anabolism have also been published, as shown in a recent meta-analysis for the benefit of HMB with resistance exercise [8]. In general, the effects are best observed in combination with physical activity or exercise in humans with anabolic resistance, like the elderly.…”
Section: Mechanism Of Actionmentioning
confidence: 99%